The Effectiveness of the Team Games Tournament (TGT) Learning Model Assisted by Fun Throw Ball on Numeracy Skills and Learning Motivation of Elementary School Students - Rizqi, Hesti Yunitiara; Suhirno, Suhirno; Setiawan, Fredy Eko (Journal of Educational Sciences, 2025)
This study aims to determine the use of the TGT learning model assisted by fun throw ball media is effective on students' numeracy skills and learning motivation. The research used is a quantitative quasi-experimental type with a nonequivalent control group design. Sampling using purposive sampling, namely class VB as the experimental group that uses the TGT learning model assisted by fun throw ball media and VA as the control group without fun throw ball media. Data analysis used normality test, homogeneity test, descriptive statistical test, independent sample t-test, and paired sample t-test. The research results show : (1) The numeracy skills of the experimental class students were better than the numeracy skills of the control class who did not receive treatment with the fun throw ball learning media (2) There was an increase in students' numeracy skills after receiving TGT learning model treatment assisted by fun throw ball media (3) Students' learning motivation increased after being given TGT learning assisted by fun throw ball media and the implementation of learning went well. Based on the results above, the use of the TGT learning model assisted by fun throw ball media is effective for students' numeracy skills and learning motivation.